Nickel oxide/graphene aerogel nanocomposite as a supercapacitor electrode material with extremely wide working potential window. (20th December 2016) - Chen, Wei; Gui, Dayong; Liu, Jianhong
Highlights: Three-dimensional nickel oxide/graphene aerogel nanocomposites (NiO/GA) were synthesized by a simple solvothermal route. The NiO/GA electrodes achieved a specific capacitance as high as 587.3 F g −1 at 1 A g −1 with an extremely wide working potential window. The cycling stability of the NiO/GA was great with a tiny decay in specific capacitance after 1000 cycles. Abstract: Three-dimensional nickel oxide/graphene aerogel nanocomposites (NiO/GA) were synthesized via a simple solvothermal-induced self-assembly process. The structural and morphological properties of the NiO/GA were characterized with XRD, FE-SEM and TEM measurements. The nickel oxide was electrochemically deposited into the highly porous GA to form NiO/GA composites. In the three-electrode system, an extremely wide working potential window was observed from −1 to 1 V in 6 M aqueous KOH. A specific capacitance as high as 587.3 F g −1 was obtained at a constant current density of 1 A g −1 . More importantly, the cycling stability of the NiO/GA was great with a tiny decay in specific capacitance after 1000 cycles at 1 A g −1 .